2014
DOI: 10.1260/1756-8277.6.2.147
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combustion Parameters on Pollutant Emissions in a Porous Burner

Abstract: This paper reports a two-dimensional numerical prediction of premixed methane/air combustion in inert porous media. The two dimensional Navier-stokes equations, the two separate energy equations for solid and gas and conservation equations for chemical species are solved using finite volume method based on SIMPLE algorithm. The burner under study is a rectangular one with two different regions. First region is a preheating zone (low porosity matrix) that followed by the actual combustion region (high porosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, the inlet mixture velocity has an impact on pollutant emissions. Khiavi numerically investigated the effects of inlet velocity on pollutant emissions, and it was found that increasing the inlet velocity of the mixture reduces NOx and CO emissions. This was attributed to the decrease in the maximum flame temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the inlet mixture velocity has an impact on pollutant emissions. Khiavi numerically investigated the effects of inlet velocity on pollutant emissions, and it was found that increasing the inlet velocity of the mixture reduces NOx and CO emissions. This was attributed to the decrease in the maximum flame temperature.…”
Section: Introductionmentioning
confidence: 99%
“…4 To prevent losses from the explosions of methaneair mixtures in underground coal mines, experimental, theoretical, and computational methods were extensively adopted by scholars to study the propagation characteristics of gas explosion. [5][6][7][8][9][10][11][12][13] Zipf et al 14 used a long tube (length, 73 m; diameter, 1.05 m) to study the deflagration-to-detonation transition of methaneair mixtures under the blockage ratios of 0.13, 0.25, and 0.50. They found that run-up length to DDT increased with the increasing of blockage ratios.…”
Section: Introductionmentioning
confidence: 99%